Baryon number violation searches in neutrino experiments. Issue 1 (28th March 2019) - Raaf, J. L.
Abstract : This paper presents a discussion of methods to search for nucleon (proton and bound neutron) decay in existing and future neutrino experiments. So far, no experiment has seen strong evidence of nucleon decay, but it is well motivated by various theoretical models, and detection would represent a profound impact on our understanding of the universe.